Correction to the article “Colorectal Screening Program in Northern Portugal: First Findings”, Published on Acta Med Port 2022 Mar;35(3):164-169. - Hugo Monteiro; Fernando Tavares; João Reis; Gustavo Ferreira; M. José Campos; Sérgio Costa; Laura Carvalho; João Carvalho; Isabel Pedroto; José Soares; Rui Henrique; Maria José Bento; et al. (Acta Médica Portuguesa, 2022)
On page 168, Table 2, where it reads: On page 168, Table 2, where it reads: Advanced phenotype rate* [n (%)] 35 (49.0) 10 (52.0) 25 (47.0) 0.606 Carcinoma** [n (%)] 2 (2.0) 1 (5.0) 1 (2.0)